'Little wake turbulence, huh?' Applying a contemporary model of learning and memory to the American Airlines Flight AA587 accident. (2nd November 2017) - Sherwin, L.; Naweed, A.
ABSTRACT: Loss of control has become a leading cause of aviation accidents and human error is often recorded as the cause in favour of other factors. This has the effect of downgrading the significance of corrective actions to address deeper systemic issues, and serves the bad-apple theory of human error. This paper uses a model of learning and memory to expand on the analysis of negative training from the AA587 accident, which documented the actions of the First Officer as the probable cause and training as contributory. Evidence from the investigation and our contemporary understanding of learning and memory is used to explain how the experiences of the First Officer fit the scenario in which the accident occurred, such that it is plausible to extend probable cause beyond his actions. The paper develops a model of causal inference that enables analysts to continue probing causality as part of a systems approach.